A multivalent antibody assembled from different building blocks using tag/catcher systems: a case study. (14th November 2022) - Schindler, Christof; Faust, Christine; Sjuts, Hanno; Lange, Christian; Kühn, Jennifer; Dittrich, Werner; Leuschner, Wulf Dirk; Schiebler, Werner; Hofmann, Joachim; Rao, Ercole; Langer, Thomas
Abstract: The field of therapeutic antibodies and, especially bi- or multispecific antibodies, is growing rapidly. Especially for treating cancers, multispecific antibodies are very promising, as there are multiple pathways involved and multispecific antibodies offer the possibility to interfere at two or more sites. Besides being used as therapeutic, multispecific antibodies can be helpful tools in basic research. However, the design and choice of the most appropriate multispecific antibody format are far from trivial. The generation of multispecific antibodies starts with the generation of antibodies directed against the desired targets and then combining the different antigen-binding sites in one molecule. This is a time-consuming and laborious approach since the most suitable geometry cannot be predicted. The SpyTag technology is based on a split-protein system, where a small peptide of said protein, the SpyTag, can bind to the remaining protein, the SpyCatcher. An irreversible isopeptide bond between the SpyTag and the SpyCatcher is formed. A related Tag-Catcher system is the SnoopTag-SnoopCatcher. These systems offer the opportunity to separately produce proteins fused to the tag-peptides and to the catcher-domains and assemble them in vitro . Our goal was to design and produce different antibody fragments, Fab domains and Fc-containing domains, with different tags and/or catchers as building blocks for the assembly of different multivalent antibodies. We have shown that large multivalent antibodies consisting of up to seven building blocks can be prepared. Binding experiments demonstrated that all binding sites in such a large molecule retained their accessibility to their corresponding antigens. Graphical Abstract: